Without Blinders: Public Values Scholarship in Political Science, Economics, and Law—Content and Contribution to Public Administration. (3rd July 2017) - de Graaf, Gjalt; van der Wal, Zeger
Abstract : How and why are public values studied within public administration's cognate disciplines? This question is addressed through a qualitative analysis of 50 public values (PVs) publications in political science, economics, and law published between 1969 and 2014. The findings show that political scientists intuitively connect PVs to the actual public rather than to government agencies and employees, whereas legal scholars often view PVs as public interests or rights. Economists are mostly concerned with how PVs can be qualified vis-à-vis private "value" and values. In short, each discipline views PVs in accordance with its key foci and epistemologies; as such, "wearing blinders" is not exclusive to one discipline. Moreover, a citation analysis shows that PVs scholars in the field of public administration seldom engage with literature from these disciplines, and vice-versa, even though doing so provides opportunities for broadening the discipline's understanding of PVs and how they conflict, across various stages and functions of policy and administration, in the pursuit of good governance.